1997
DOI: 10.1093/ajcn/66.5.1116
|View full text |Cite
|
Sign up to set email alerts
|

Lactation and weight retention

Abstract: The effect of lactation on weight retention was investigated longitudinally, with data collected at 0.5, 2, 4, 6, 12, and 18 mo after parturition in 110 women aged 20-40 y who had been nulliparous or primiparous. At each evaluation women were categorized as fully breast-feeding, partly breast-feeding, or bottle-feeding including infants weaned to a bottle (bottle feeding/weaned). Postpartum weight retention was calculated by subtracting weight before pregnancy from weight at each evaluation. Lactation practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
123
2
17

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(154 citation statements)
references
References 29 publications
12
123
2
17
Order By: Relevance
“…Most studies included primarily adult women. 23,[27][28][29][31][32][33]35,36,38,43,46 Four studies reported a mean age above 30 years, 23,27,28,36,46 one study below 20 years. 42 Two studies did not provide any information on their population's age 24,44 (Table 1).…”
Section: Qualitative Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies included primarily adult women. 23,[27][28][29][31][32][33]35,36,38,43,46 Four studies reported a mean age above 30 years, 23,27,28,36,46 one study below 20 years. 42 Two studies did not provide any information on their population's age 24,44 (Table 1).…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…Tables 1-3 summarize the results of the qualitative analysis. Fifteen prospective studies, 23,24,[29][30][31][32][33][34][35][36]38,[40][41][42][43][44][45] five retrospective studies, 22,[25][26][27][28]37,46 and the control group from a randomized controlled trial 39 were included in the final analysis. Studies in which women were recruited around the time of delivery and then followed prospectively for postpartum body weight (ambivalent design, as baseline weight was assessed retrospectively) 24,29,30,[34][35][36][44][45][46] were considered as prospective in design, as we wanted to focus on the development of postpartum weight change.…”
Section: Qualitative Resultsmentioning
confidence: 99%
See 3 more Smart Citations